Weight following birth and childhood dietary intake: A prospective cohort study - Fonseca, MJ (2017)
Objectives: Unhealthy childhood dietary habits track through life and are independent and modifiable risk factors for disease. Therefore, it is essential to understand the factors involved. We aimed to evaluate the associations of birthweight (BW) and newborn weight change (NWC) during the first 96 h of life and childhood longitudinal weight trajectories with dietary intake at age 4. Methods: As part of the Generation XXI birth cohort (G21), children were recruited in 2005 and 2006 at all public units providing obstetrical and neonatal care in Porto, Portugal. Information was collected by face-to-face interview and abstracted from clinical records. At age 4, weight measurements recorded from birth to current age were abstracted and weight trajectories estimated. Food frequency questionnaires were applied, and three dietary patterns (DPs) were identified: “Energy-dense food (EDF)+Dairy,” “Lower in Healthy Food,” and “Healthier.” Logistic regression models were used to compute the odds ratio (OR) and 95% confidence intervals (CIs) (OR [95% CI]) in a sample of 775 children. Results: Children with higher BW were less frequently in the “EDF+Dairy” DP (0.94 [0.89–0.98] per 100 g increase in BW). Children with higher NWC had lower odds of eating fruit ≥3/d (0.93 [0.87–0.99] per 1% increase in NWC). Children with higher weight during childhood had higher odds of belonging to the “EDF+Dairy” DP (1.90 [1.04–3.47]) and lower odds of eating vegetable soup ≥2/d (0.56 [0.34–0.91]). Children showing catch-up grow in the first year of life had higher odds of eating dairy products ≥3/d (3.76 [1.31–10.80]). Conclusions: The way that children grow during childhood played a major role on dietary intake at age 4.